A Comprehensive Review on Efficiency Enhancement of Solar Collectors Using Hybrid Nanofluids - Mahamude, Abu Shadate Faisal; Muhamad Kamal, Kamarulzaman; Wan Sharuzi, Wan Harun; Kumaran, Kadirgama; Devarajan, Ramasamy; Farhana, Kaniz; Rosli, Abu Bakar; Yusaf, Talal; Subramanion, Sivarao; Yousif, Belal (MDPI AG, 2022)
Because of its potential to directly transform solar energy into heat and energy, without harmful environmental effects such as greenhouse gas emissions. Hybrid nanofluid is an efficient way to improve the thermal efficiency of solar systems using a possible heat transfer fluid with superior thermo-physical properties. The object of this paper is the study the latest developments in hybrid applications in the fields of solar energy systems in different solar collectors. Hybrid nanofluids are potential fluids with better thermo-physical properties and heat transfer efficiency than conventional heat transfer fluids (oil, water, ethylene glycol) with single nanoparticle nanofluids. The research found that a single nanofluid can be replaced by a hybrid nanofluid because it enhances heat transfer. This work presented the recent developments in hybrid nanofluid preparation methods, stability factors, thermal improvement methods, current applications, and some mathematical regression analysis which is directly related to the efficiency enhancement of solar collector. This literature revealed that hybrid nanofluids have a great opportunity to enhance the efficiency of solar collector due to their noble thermophysical properties in replace of conventional heat transfer working fluids. Finally, some important problems are addressed, which must be solved for future study